Flow structures in evolving scour holes caused by a plunging jet downstream of a weir - Si, Jin-Hua (2020)
Particle image velocimetry was used to measure the flow structures in evolving scour holes caused by a plunging jet downstream of a weir. The results clearly depict that four different types of roller were involved in scour development and the scour wes mainly caused by the major roller. The average kinetic energy (AKE) distributions reveal that the rollers were maintained by jet impingements on both the concave scoured bed and the water surface. The gap gradually enlarged between jet regions with high transport capability, which adversely affected scour development. The turbulence kinetic energy (TKE) dissipated along the main jet direction. As the scour hole developed, the regions of significant TKE moved successively away from the bed with a reduction in scour rate. The plunging jet zone had negative Reynolds shear stress (RSS), and absolute values there were larger than in other zones in the scour hole. Meanwhile, the regions of significant positive RSS changed in size and location with scour development.